The novel peptide NbPPI1 identified from Nicotiana benthamiana triggers immune responses and enhances resistance against Phytophthora pathogens. Issue 5 (15th March 2021) - Wen, Qujiang; Sun, Manli; Kong, Xianglan; Yang, Yang; Zhang, Qiang; Huang, Guiyan; Lu, Wenqin; Li, Wanyue; Meng, Yuling; Shan, Weixing
Abstract: In plants, recognition of small secreted peptides, such as damage/danger‐associated molecular patterns (DAMPs), regulates diverse processes, including stress and immune responses. Here, we identified an SGPS (Ser‐Gly‐Pro‐Ser) motif‐containing peptide, Nicotiana tabacum NtPROPPI, and its two homologs in Nicotiana benthamiana, NbPROPPI1 and NbPROPPI2. Phytophthora parasitica infection and salicylic acid (SA) treatment induced NbPROPPI1/2 expression. Moreover, SignalP predicted that the 89‐amino acid NtPROPPI includes a 24‐amino acid N‐terminal signal peptide and NbPROPPI1/2‐GFP fusion proteins were mainly localized to the periplasm. Transient expression of NbPROPPI1/2 inhibited P. parasitica colonization, and NbPROPPI1/2 knockdown rendered plants more susceptible to P. parasitica . An eight‐amino‐acid segment in the NbPROPPI1 C‐terminus was essential for its immune function and a synthetic 20‐residue peptide, NbPPI1, derived from the C‐terminus of NbPROPPI1 provoked significant immune responses in N. benthamiana . These responses led to enhanced accumulation of reactive oxygen species, activation of mitogen‐activated protein kinases, and up‐regulation of the defense genes Flg22‐induced receptor‐like kinase ( FRK ) and WRKY DNA‐binding protein 33 ( WRKY33 ). The NbPPI1‐induced defense responses require Brassinosteroid insensitive 1‐associated receptor kinase 1 ( BAK1 ). These results suggest that NbPPI1 functions as a DAMP in N. benthamiana ; this novel DAMP provides a potentially useful target for improving plant resistance to Pytophthora pathogens. Abstract : The Nicotiana benthamiana damage‐induced molecular pattern (DAMP) peptide NbPROPPI1 induces robust basal immune responses, including enhanced reactive oxygen species accumulation, activation of MAPKs, and up‐regulation of defense genes. NbPROPPI1 has a potential to facilitate development of broad‐spectrum disease resistance in crops.